Peripheral Ameloblastoma of Upper Gingiva in a Patient with Port-Wine Stain - Natheer H. Al-Rawi; Sahar Othman; Ab Rani Samsudin (Case Reports in Medicine)
The peripheral ameloblastoma (PA), also known as extraosseous ameloblastoma, is a rare soft tissue tumor of odontogenic origin, accounting for 1–5% of all ameloblastoma. In some cases, saucerization of underlying bone is the only radiological evidence of this lesion, and PA has identical histological characteristics of intraosseous ameloblastoma. However, it is slow growing, less aggressive, and less invasive in nature. The present report describes a rare case of PA in the maxillary labial gingiva of a 37-year-old man with port-wine vascular malformation. PA was clinically diagnosed as a pyogenic granuloma, and following the surgical treatment of the lesion, its histological features were of ameloblastoma. This case illustrates the importance of including peripheral ameloblastoma in the differential diagnosis of painless exophytic gingival swelling.